(untitled) (Historia, 2021)
Local history remains a dynamic meeting place between the man on the street and the discipline of history. The popularity of this field and its potential for academic enterprise has been exploited by numerous researchers at South African universities as well as the Human Sciences Research Council. The spin-offs are now beginning to gain momentum.